N.I. VAVILOV, THE FOUNDER OF THE CENTRAL PLANT BREEDING AND GENETICAL STATION. ON THE 90th ANNIVERSARY OF VIR PUSHKIN LABORATORIES - E. V. Truskinov (Вавиловский журнал генетики и селекции)
The outstanding activity of N.I. Vavilov shows that he was not only a great scientist but also a remarkable science manager. He founded the All-Russia Institute of Plant Industry (VIR) and a network of experimental stations. The first of them, the most beloved and patronized, was the Central Plant Breeding and Genetical Station in Detskoe Selo (presently Pushkin, a municipal town in Pushkinsky raion, St. Petersburg). It was founded 90 years ago, on May 20, 1921. On January 1, 1939, it was renamed to VIR Pushkin Laboratories. The article describes its foundation and history before Vavilov’s arrest in 1940.